Effect of the away goal rule on the technical performance of football teams in the UEFA Champions League - Kubayi, A.; Stone, J. A. (International Journal of Performance Analysis in Sport, 2025)
Despite significant debate surrounding UEFA`s removal of the away goal rule in 2021, its impact on technical performance has not been studied. Therefore, this study aimed to investigate how selected technical performance indicators were impacted by the change in the away goal rule during the UEFA Champions League. Data were sourced via the Wyscout platform. The sample consisted of 112 UEFA Champions League games played during the knock-out stages of the competition, in which 56 games were played during seasons with an away goal rule (2017-2018 and 2018-2019) and 56 were played in seasons without an away goal rule (2021-2022 and 2022-2023). The findings showed that the removal of the away goal rule was accompanied by significant (p < 0.05) decreases in average pass length, long passes, progressive passes, passes to the final third, offsides, duels, duels won, and counterattacks. Furthermore, a significant (p < 0.05) interaction was found between the away goal rule and the leg of competition, affecting the number of counterattacks with shots. Therefore, UEFA should take cognisant of the present findings when considering the use of the away goal rule in future competitions.